KONSEPSI MANAJEMEN MUTU DALAM PENDIDIKAN - Abdul Hadi (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract:This journal focuses on the quality of professionally managed educational institutions through integrated quality management. Educational institutions as producer services sector should pay attention to quality; quality of managerial and academic aspects. These two aspects can be achieved through the application of the concept of total quality management (TQM). TQM is a management concept that places all insan (civitass academica) of higher education institutions as individuals who have responsibility for quality in accordance with their duties and functions. TQM is an approach to doing business that seeks to maximize the competitiveness of institutions through continuous improvement of products, services, people, processes and the environment. TQM is the starting point for improving quality that will be under the jargon of